Rheological and Structural Properties of Camel Milk/Sweet Potato Starch Gel - A. A. Mohamed; S. Hussain; M. S. Alamri; M. A Ibraheem; Akram A. Abdo Qasem; Omar A. Alhaj; Mohammad A. Alshuniaber (Journal of Chemistry)
The unique composition of camel milk limited its use for fermented products preparation. In this research, camel milk (CAM) or cow milk (COM) was blended with sweet potato starch (SPS). Blends were precooked and the rheological properties of the gel were determined. Since the elastic modulus (G′) was much greater than the viscous modulus (G″), milk + SPS gels are considered viscoelastic. The tan δ of all blends was <1.0, signifying solid-like behavior; however, variations between CAM gels or COM were identified. Unlike COM, CAM was more frequency-dependent at low frequencies (0.1 to 1.0 rad/sec). Gels exhibited shear thinning according to the nonlinear rheological tests. Camel milk exhibited gel hardness much higher than cow milk. Because of the domination of G′ and the low power law exponent, camel milk is expected to present processing complications such as in extrusion cooking.